2004
DOI: 10.1021/jp036651+
|View full text |Cite
|
Sign up to set email alerts
|

Binding Kinetics and SWNT Bundle Dissociation in Low Concentration Polymer−Nanotube Dispersions

Abstract: Single-wall carbon nanotubes are severely restricted by the fact that they exist in bundles. In addition, their interaction with other materials is poorly understood. In this work a new spectroscopic method is described to measure the ratio of free polymer to nanotube-bound polymer in SWNT/polymer solutions. This ratio is highly nonlinear and can be described by a model based on polymer−nanotube adsorption/desorption kinetics. In combination with the experimental data, this model shows that the nanotube bundle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(142 citation statements)
references
References 19 publications
9
133
0
Order By: Relevance
“…As can be seen in Fig. 3 the emission ratio plots follow an approximate trend to that proposed by the original model (Coleman et al, 2004). However, a significant degree of deviation from the model fit can be observed.…”
Section: Spectroscopic Analysismentioning
confidence: 63%
See 2 more Smart Citations
“…As can be seen in Fig. 3 the emission ratio plots follow an approximate trend to that proposed by the original model (Coleman et al, 2004). However, a significant degree of deviation from the model fit can be observed.…”
Section: Spectroscopic Analysismentioning
confidence: 63%
“…This increased degree of deviation can be attributed to the increased variability introduced to the system by the filtration and centrifugation process. Despite the inability to reliably fit the data to the model proposed by Coleman et al (2004) it can be clearly seen in the ratio plots of Fig. 3 that the incorporation and removal of the carbon based nanoparticles into the medium altered its emission characteristics giving further supportive evidence for the alteration of the medium upon interaction with the SWCNT.…”
Section: Spectroscopic Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…Another study did not present the data in the appropriate graphical format (the x-axis was presented in terms of added polymer and not equilibrium polymer) but enough information was given so that such a plot could be constructed. 23 In another study where the nanotubes were dispersed in solution, 24 the authors presented the ratio adsorbed polymer/ total polymer (from which the adsorbed amount could be calculated); however the x-axis was also presented in terms of amount added instead of amount in solution after absorption, and the polymer:nanotube mass ratio was fixed at 1:1. The authors showed that there was a relative maximum in the ratio adsorbed polymer/total polymer at an added polymer or nanotube concentration of about 10 À4 kg/m 3 , while a relative minimum occurred at about 10 À3 kg/m 3 .…”
Section: Reviewmentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNT) have generated much interest in recent years due to their unique properties and huge potential for applications 1 . However, some fundamental problems remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%